Analisis Yuridis terhadap Penerapan Sanksi Pidana pada Kasus Kekerasan dalam Rumah Tangga - Agus Irawan; M. Rezky Paturahmat; Ratno Timur; Tantan Rustandi; Albi Ternando; Reanto Agam Rustandi (Universitas Batanghari Jambi, 2026)
Indonesia, based on Pancasila as a state based on law, affirms the principle of the supremacy of law as stated in Article 1 paragraph (3) of the 1945 Constitution. Domestic violence (KDRT) is a legal violation that often affects women as victims. Law Number 23 of 2004 concerning the Elimination of Domestic Violence (KDRT) aims to provide legal protection and establish strict criminal sanctions for perpetrators. This study aims to analyze the legal review of criminal sanctions in cases of domestic violence and assess whether the sanctions imposed have met the objectives of law enforcement and a sense of justice for victims. The method chosen is normative legal research that prioritizes legal principles and analyzes statutory regulations. The results of the study indicate that criminal sanctions in cases of domestic violence are in accordance with the objectives of law enforcement to protect victims. Law No. 23 of 2004 is designed to provide a deterrent effect on perpetrators. However, the effectiveness of sanctions is highly dependent on consistent law enforcement and support for victims and the rehabilitation of perpetrators. A holistic approach is needed to overcome systemic barriers and achieve justice.